Peran Pertanian Urban Pada Kesejahteraan Petani Muslim Pada Empat Kelompok Tani Di Surabaya Ditinjau Dari Perspektif Islam - Trisna Setia Permana; Moh. Qudsi Fauzy (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
This study aimed to describe the role of urban farming in the welfare of the Muslim farmers in four farmer groups in Surabaya from the perspective of Islam. This study used descriptive qualitative approach with case study strategy. The data authenticity technique using construct validity tactics with multiple sources of evidence. The analysis technique using pattern matching logic. The results showed the positive role of urban farming in the material welfare, namely: the creation of job opportunities and self-employment, the creation of small businesses in the agricultural sector and the informal sector, and increase the income of the four members of farmer groups; whereas the non-material welfare, namely: produce farmed commodities and processed products that is classified as halal, income which does not contain usury, implementing the principles of honesty and fairness principles in marketing, as well as undertake community development activities such as counseling and training.